SerpinA5 Inhibits Malignant Biological Behavior of Esophageal Squamous Cell Carcinoma by Regulating Fn/Integrin-β1 Signaling Pathway - Yu WEI; Zhouhua ZHANG; Zhifang LI; Li ZHANG (Zhongliu Fangzhi Yanjiu)
ObjectiveTo investigate the effect of SerpinA5 on the malignant biological behavior of esophageal squamous cell carcinoma (ESCC) and its molecular mechanism. MethodsThe expression levels of the SerpinA5 gene in various tumors and adjacent normal tissues were analyzed by using the TIMER2.0 database. The expression levels of SerpinA5 in the ESCC cell line and esophageal epithelial cells were detected through Western blot analysis. Stably transfected KYSE150 cell line with overexpression of SerpinA5 was constructed through lentiviral transfection, and overexpression efficiency was detected via Western blot analysis. The effects of SerpinA5 overexpression on the proliferation, apoptosis, migration, and invasion of ESCC cells were detected by employing the CCK8, plate cloning, flow cytometry, wound healing, and Transwell invasion assays. The nude mice subcutaneous xenograft model with SerpinA5 overexpression was constructed. Tumor growth was observed, and tumor volume and mass were measured. The cell proliferation level of the subcutaneous xenograft tumors in nude mice was detected via immunohistochemistry (IHC). Coimmunoprecipitation (Co-IP) was employed to determine the interaction between SerpinA5 and Fn. Western blot analysis was applied to detect the expression levels of proteins (Fn, Integrin-β1, FAK, and p-FAK) related to the Fn/Integrin-β1 signaling pathway in transplanted tumors. ResultsSerpinA5 was expressed at low levels in ESCC tissues and cell lines. In ESCC cells, SerpinA5 overexpression can considerably inhibit cell proliferation, migration, and invasion and promote cell apoptosis. In the subcutaneous xenograft experiment on nude mice, the tumor volume and weight of the SerpinA5 overexpression group were lower than those of the negative control group. IHC results demonstrated that SerpinA5 overexpression significantly inhibited the proliferation of ESCC cells in tumor tissues. Co-IP confirmed the interaction between SerpinA5 and Fn. Western blot analysis results showed that the expression levels of Fn, Integrin-β1, and p-FAK in the Fn/Integrin-β1 signaling pathway of ESCC cells in the subcutaneous xenograft tumors of nude mice significantly decreased after SerpinA5 overexpression. ConclusionSerpin A5 may inhibit proliferation, migration, and invasion and promote apoptosis of ESCC cells by regulating the Fn/Integrin-β1 signaling pathway.